Modulations of Neuroendocrine Stress Responses During Confinement in Antarctica and the Role of Hypobaric Hypoxia - Strewe, Claudia; Thieme, Detlef; Dangoisse, Carole; Fiedel, Barbara; van den Berg, Floris; Bauer, Holger; Salam, Alex P.; Gössmann-Lang, Petra; Campolongo, Patrizia; Moser, Dominique; Quintens, Roel; Moreels, Marjan; et al. (Frontiers in Physiology, 2018)
The Antarctic continent is an environment of extreme conditions. Only few research stations exist that are occupied throughout the year. The German station Neumayer III and the French-Italian Concordia station are such research platforms and human outposts. The seasonal shifts of complete daylight (summer) to complete darkness (winter) as well as massive changes in outside temperatures (down to -80 °C at Concordia) during winter result in complete confinement of the crews from the outside world. In addition, the crew at Concordia is subjected to hypobaric hypoxia of 650 hPa as the station is situated at high altitude (3,233 m). We studied three expedition crews at Neumayer III (sea level) (n = 16) and two at Concordia (high altitude) (n = 15) to determine the effects of hypobaric hypoxia on hormonal/metabolic stress parameters (endocannabinoids, catecholamines, glucocorticoids) and evaluated the psychological stress over a period of 11 months including winter confinement. In the Neumayer III (sea level) crew endocannabinoid (EC) and n-acylethanolamide (NAE) concentrations increased significantly already at the beginning of the deployment (p < 0.001) whereas catecholamines and cortisol remained unaffected. Over the year ECs and NAEs stayed elevated and fluctuated before slowly decreasing till the end of the deployment. The classical stress hormones showed small increases in the last third of deployment. In contrast, at Concordia (high altitude) norepinephrine concentrations increased significantly at the beginning (p < 0.001) which was paralleled by low EC levels. Prior to the second half of deployment norepinephrine declined constantly to end on a low plateau level whereas then the EC concentrations increased significantly in this second period during the overwintering (p < 0.001). Psychometric data showed no significant changes in the crews at either station. These findings demonstrate that exposition of healthy humans to the physically challenging extreme environment of Antarctica i) has a distinct modulating effect on stress responses. Additionally, ii) acute high altitude/hypobaric hypoxia at the beginning seem to trigger catecholamine release that downregulates the EC response. These results iii) are not associated with psychological stress.